Current Issues in the Classification of Psychotic Major Depression - Keller, Jennifer (Oxford University Press, 2007)
Depression is one of the most common mental disorders worldwide. There are a number of depression subtypes, and there has been much debate about how to most accurately capture and organize the features and subtypes of major depression. We review the current state of categorizing unipolar major depression with psychotic features (psychotic major depression, PMD), including clinical, biological, and treatment aspects of the disorder. We then propose some improvements to the current unipolar major depression categorization system. Finally, we identify important issues in need of further research to help elucidate the subtype of unipolar PMD.